2015
DOI: 10.3945/ajcn.114.105833
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil–derived n−3 PUFA therapy increases muscle mass and function in healthy older adults

Abstract: Fish oil-derived n-3 PUFA therapy slows the normal decline in muscle mass and function in older adults and should be considered a therapeutic approach for preventing sarcopenia and maintaining physical independence in older adults. This study was registered at clinicaltrials.gov as NCT01308957.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
409
1
16

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(442 citation statements)
references
References 43 publications
16
409
1
16
Order By: Relevance
“…Studies in older adults have reported beneficial impacts of n-3 FA supplementation on reducing/reversing the loss of muscle mass and function over a 6 month intervention period (Smith et al, 2015), have demonstrated a modest improvement in muscle quality (torque per unit cross sectional area) in older females, or have demonstrated no benefit beyond training alone in older males (Da Boit et al, 2017). Other studies report no effect of n-3 FA intake on endurance exercise performance or recovery after 4-10 wk of training (Buckley et al, 2009;Guzman et al, 2011;Raastad et al, 1997;Walser & Stebbins, 2008), and no impact of n-3 FA intake on improvements in high intensity treadmill running capacity following 4 wk of training in recreationally active males and females (Huffman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in older adults have reported beneficial impacts of n-3 FA supplementation on reducing/reversing the loss of muscle mass and function over a 6 month intervention period (Smith et al, 2015), have demonstrated a modest improvement in muscle quality (torque per unit cross sectional area) in older females, or have demonstrated no benefit beyond training alone in older males (Da Boit et al, 2017). Other studies report no effect of n-3 FA intake on endurance exercise performance or recovery after 4-10 wk of training (Buckley et al, 2009;Guzman et al, 2011;Raastad et al, 1997;Walser & Stebbins, 2008), and no impact of n-3 FA intake on improvements in high intensity treadmill running capacity following 4 wk of training in recreationally active males and females (Huffman et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Smith et al [139] previously published novel evidence supporting the efficacy of n-3 fatty acid supplementation on its role in increasing muscle anabolic signalling activity and stimulating MPS above basal postabsorptive values in older adults. In a recently published RCT, Smith et al [140] further showed that a 6-month n-3 fatty acid intervention, without exercise, had statistical and clinically beneficial effects on attenuating sarcopenic symptomology by increasing thigh muscle volume (3.6%; 95% CI: 0.2-7.0%), hand-grip strength (2.3kg; 95% CI: 0.8-3.7kg) and upper/lower body 1-RM muscle strength (4.0%; 95% CI: 0.8-7.3%) (all p <0.05). Furthermore, Rodacki et al [141] previously reported that n-3 fatty acid supplementation augments exercise induced changes in muscle strength and physical performance.…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%
“…Despite the exact mechanisms being unclear, the investigators of these studies identified that the anabolic effects of n-3 fatty acids are independent of any significant influence on inflammation. Rather, they likely involve alterations in both anabolic and catabolic pathways, improved mitochondrial functioning and biogenesis, neuroprotection and motor-neuron excitability properties [139][140][141].…”
Section: Underlying Mechanisms Underpinning the Potential Benefits Ofmentioning
confidence: 99%
“…Therefore, it has been speculated that older adults with sarcopenia would also benefit from more omega-3 fatty acids consumption, since inflammation is one of the underlying pathophysiological events during the disease process [15,111]. Furthermore, it has been shown that the anabolic response of skeletal muscle to AA administration may be enhanced by combining with omega-3 fatty acids supplementation [15,117]. Smith et al [15] conducted a study with 16 healthy older adults, aged 65 years or more, to investigate whether supplementation with omega-3 fatty acids for 8 weeks had any impact on the rate of MPS and anabolic signaling.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…In fact, consumptions of omega-3 fatty acids have been shown to improve muscle function by enhancing muscle strength and performance [117][118][119][120]. Another study by Smith et al [117] demonstrated that supplementation with omega-3 fatty acids [four 1 g pills per day, providing 1.86 g eicosapentaenoic acid (EPA; 20:5n-3)/day and 1.5 g docosahexaenoic acid (DHA; 22:6n-3)/day] for 6 months not only increases thigh muscle volume, but also enhances hand grip strength and average isokinetic power [117]. Similarly, dietary assessments of nearly 3000 elderly men and women have shown positive associations between fatty fish consumption and grip strength in both genders [118].…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%